1992
DOI: 10.1128/aac.36.6.1290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a human antiflagellar monoclonal antibody in combination with antibiotics on Pseudomonas aeruginosa infection

Abstract: The in vivo activity of human immunoglobulin M monoclonal antibody IN-2A8, which is specific for flagellum type b ofPseudomonas aeruginosa, was evaluated in comparison to anti-O antigen (serotype B) MAb KO-2F2 and in combination with antibiotics. IN-2A8 showed stronger activity than KO-2F2 against subcutaneous infection in burned mice, while it was much less active against intraperitoneal infection in normal mice. In a burn infection model, IN-2A8 inhibited the increase of bacteria in skin lesions weakly and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Challenge of leukopenic mice by i.p. injection with P. aeruginosa was reported to cause sepsis by acute systemic infection, leading to the death of mice within 1 to 3 days after infection (32,56). In our in vivo model, leukopenic mice infected i.p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenge of leukopenic mice by i.p. injection with P. aeruginosa was reported to cause sepsis by acute systemic infection, leading to the death of mice within 1 to 3 days after infection (32,56). In our in vivo model, leukopenic mice infected i.p.…”
Section: Discussionmentioning
confidence: 99%
“…This model has been developed to study the pathogenesis of P. aeruginosa infection under immunosuppressed conditions and to evaluate therapeutic agents (10,56). Challenge of leukopenic mice by i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Challenge of leucopenic mice by i.p. injection with P. aeruginosa was reported to cause sepsis by acute systemic infection, leading to the death of mice within 1 to 3 days after infection (Miyazaki et al, 1995;Uezumi et al, 1992). We previously demonstrated that EprS activates NF-kB-driven promoter through PAR-1, -2, or -4 and induces IL-8 production through PAR-2 in a human bronchiole epithelial cell line (Kida et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…6). This model has been developed to study the pathogenesis of P. aeruginosa infection under immunosuppressed conditions and to evaluate the therapeutic agents (Cryz et al, 1983;Uezumi et al, 1992). Challenge of leucopenic mice by i.p.…”
Section: Discussionmentioning
confidence: 99%
“…208 Similarly, several antibodies targeting other virulence-associated antigens of P. aeruginosa such as flagella, 75,78,79,[209][210][211][212] …”
Section: Acknowledgmentsmentioning
confidence: 99%